Functional Conservation of LncRNA JPX Despite Sequence and Structural Divergence. Issue 2 (17th January 2020) - Karner, Heather; Webb, Chiu-Ho; Carmona, Sarah; Liu, Yu; Lin, Benjamin; Erhard, Micaela; Chan, Dalen; Baldi, Pierre; Spitale, Robert C.; Sun, Sha
Abstract: Long noncoding RNAs (lncRNAs) have been identified in all eukaryotes and are most abundant in the human genome. However, the functional importance and mechanisms of action for human lncRNAs are largely unknown. Using comparative sequence, structural, and functional analyses, we characterize the evolution and molecular function of human lncRNA JPX . We find that human JPX and its mouse homolog, lncRNA Jpx, have deep divergence in their nucleotide sequences and RNA secondary structures. Despite such differences, both lncRNAs demonstrate robust binding to CTCF, a protein that is central to Jpx 's role in X chromosome inactivation. In addition, our functional rescue experiment using Jpx -deletion mutant cells shows that human JPX can functionally complement the loss of Jpx in mouse embryonic stem cells. Our findings support a model for functional conservation of lncRNAs independent from sequence and structural divergence. This study provides mechanistic insight into the evolution of lncRNA function. Graphical abstract: Image 1 Highlights: Comparison of human JPX with its mouse homolog reveals rapid sequence evolution. Human JPX shows RNA secondary structure divergent from mouse Jpx . Human JPX RNA and mouse Jpx RNA both bind CTCF. Human JPX rescues Jpx -deletion defects in mouse ES cells.